Loo with a view: managing snow-based backcountry visitors' remote toileting experiences. Issue 3 (3rd July 2022) - Smart, Jen; Wolf, Isabelle; Scherrer, Pascal
ABSTRACT: The dual mandate of conserving natural and/or cultural heritage while facilitating visitor experiences challenges protected area managers to deal with the environmental impacts of human behaviours. The issue of waste disposal is an important aspect of the human-nature interaction, not least in backcountry areas, yet it is a largely understudied aspect of winter recreation management. To address this gap in knowledge, this study examines remote toileting practices of snow-based visitors travelling and camping in Kosciuszko National Park, Australia. Using recreation specialisation as a theoretical framework for understanding and segmenting users, we examined toileting behaviour of snow-based backcountry visitors. The study highlights that toileting behaviour of snow-based backcountry travellers varies with the level of specialisation. Experts were more willing to carry out waste while those with intermediate experience relied more on infrastructure-intensive forms of waste disposal or buried waste in snow. Adoption of carry-out practices, nonetheless, were low in both segments. Length and place of stay were also important factors. A multi-faceted communication approach targeted at multi-day visitors and promoting carry-out strategies supported by targeted entry-point infrastructure is recommended for effective management.